2017
DOI: 10.1021/acs.jafc.7b00576
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Simultaneous Analysis of 360 Pesticides in Brown Rice, Spinach, Orange, and Potato Using Microbore GC-MS/MS

Abstract: A multiresidue method for the simultaneous and rapid analysis of 360 pesticides in representative agricultural produce (brown rice, orange, spinach, and potato) was developed using a modified QuEChERS procedure combined with gas chromatography-tandem mass spectrometry (GC-MS/MS). Selected reaction monitoring transition parameters (e.g., collision energy, precursor and product ions) in MS/MS were optimized to achieve the best selectivity and sensitivity for a wide range of GC-amenable pesticides. A short (20 m)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 54 publications
1
38
1
1
Order By: Relevance
“…Moreover, the analytical method developed was linked with other gas (GC) and liquid chromatography (LC) methods reported in the literature for pesticide quantification in vegetables, Table 4 [1,3,5,8,12,16,[31][32][33][34][35]. The sample amount (g), LOD, LOQ and recovery (analytical performance) were considered to demonstrate the advantages of the QuEChERS-dSPE/UHPLC-PDA method here validated.…”
Section: Methods Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the analytical method developed was linked with other gas (GC) and liquid chromatography (LC) methods reported in the literature for pesticide quantification in vegetables, Table 4 [1,3,5,8,12,16,[31][32][33][34][35]. The sample amount (g), LOD, LOQ and recovery (analytical performance) were considered to demonstrate the advantages of the QuEChERS-dSPE/UHPLC-PDA method here validated.…”
Section: Methods Validationmentioning
confidence: 99%
“…Therefore, it is crucial to regulate such contaminants in food, and to determine if they pose any danger to public health and to the environment. In this scenario, to guarantee that levels of insecticide residues on vegetables are safe, they must meet current tolerances or maximum residue limits (MRLs, Table 1), normally in µg/kg, which are strictly set by the European Union (EU), Codex Alimentarius (CA) and other organizations [6,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trifloxystrobin is a broad‐spectrum antifungal, whose EE isomer is responsible for biological activity . The 1,2,4‐triazoles 1 and 2 are both known antifungal pesticides, which, like the more popular 1,2,4‐triazole antifungals fluconazole ( 4 ) and posaconazole ( 5 , MMV688774), inhibit CYP51 in the sterol biosynthesis pathway. CYP51 has been validated as a target in T. brucei , with 5 displaying the capacity to inhibit the Tb variant of this enzyme, while X‐ray co‐crystal studies of CYP51 from T. cruzi and T. brucei with compounds 4 (PDB IDs: https://www.rcsb.org/structure/2WX2 and https://www.rcsb.org/structure/2WUZ) and 5 (PDB ID: https://www.rcsb.org/structure/3K1O) indicate that the respective active sites are nearly identical .…”
Section: Kinetoplastids (Trypanosomiasis and Leishmaniasis)mentioning
confidence: 99%
“…3) indicated that the signals of most analytes were enhanced by co-eluent matrices throughout the t R . Many previous studies have reported signal enhancement by crop matrices in GC-MS or GC-MS/MS [22][23][24]. The average matrix effect for target pesticides was 5.5%.…”
Section: Matrix Effectmentioning
confidence: 85%